Exploring the Role of AI-Driven Speech Recognition System in Supporting Inclusive Education for Hearing Impaired Students in Pakistan - Aftab, Muhammad Javed; Amjad, Faisal; Chaudhry, Hira (Annals of Human and Social Sciences, 2024)
This study investigates how AI-driven speech recognition systems can make inclusive education better for hearing impaired students in Pakistan. The research, which uses a quantitative approach with a descriptive survey method, is based on teachers’ opinions on the effectiveness of these technologies. We randomly selected 240 teachers from general schools to gather their perspectives on the advantages and challenges of AI-driven speech recognition systems. We gave rational people two options for answering the questionnaire, both in person and online, to ensure representation from a variety of educational settings. The results confirm that these technologies significantly improved class participation, listening to commands and other activities, and increased inclusivity for hearing-impaired students. Particularly the ones with more practice, mostly instructors in rural areas, showed a better reaction to the machines. The study is a sign that there is a need for specialized training and adequate strategies to make the most of AI systems in diverse educational settings. Suggestions include creating preferential training sessions, targeting distinct integration strategies based on individual school environments, and providing affixed support for these systems. Further, this research for information systems professionals will focus on conducting further investigation into the effects of AI-driven speech recognition on deafness, including the use of advanced technology in the development of future inclusive educational systems.